2021
DOI: 10.1002/rsa.21011
|View full text |Cite
|
Sign up to set email alerts
|

Upper tail for homomorphism counts in constrained sparse random graphs

Abstract: Consider the upper tail probability that the homomorphism count of a fixed graph H within a large sparse random graph Gn exceeds its expected value by a fixed factor 1+δ. Going beyond the Erdős–Rényi model, we establish here explicit, sharp upper tail decay rates for sparse random dn‐regular graphs (provided H has a regular 2‐core), and for sparse uniform random graphs. We further deal with joint upper tail probabilities for homomorphism counts of multiple graphs H1,…,Hk (extending the known results for k=1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…For EN 2 , we observe that there are O(n 7 ) ways to specify a pair of intercalates that share two edges, and each such pair is present in G with probability (α/n) 6 . There are…”
Section: A Concentration Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…For EN 2 , we observe that there are O(n 7 ) ways to specify a pair of intercalates that share two edges, and each such pair is present in G with probability (α/n) 6 . There are…”
Section: A Concentration Inequalitymentioning
confidence: 99%
“…We remark that as a naïve approach to try to prove Theorem 1.2, we might try to study the independent random hypergraph model mentioned earlier (in which each edge is present with probability 1/n independently), and to condition on the (hopefully not too unlikely) event that our random hypergraph is in fact a Latin square. For example, it is possible to study large deviations in random regular graphs with a related approach [6,26] (although the details are highly nontrivial). However, the property of being a Latin square is extremely restrictive, and there does not seem to be any simple independent model that produces a Latin square property with probability greater than about (1/ √ n) n 2 (which is vanishingly small compared to the large deviation probabilities in Theorem 1.2(a-b)).…”
Section: Introductionmentioning
confidence: 99%
“…for all fixed δ > 0 and p ≥ C(δ)n −1 log n. (DeMarco-Kahn actually showed the stronger result that one can take C(δ) = 1 in the earlier expression.) Chatterjee and Dembo [5] managed to improve the large deviation principle so that it applies when p → 0 polynomially with n. Lubetzky and Zhao [14] were able to solve the resulting variational problem in the case of triangles, and were able to use the Chatterjee-Dembo result to show that Pr[T n,p ≥ (1 + δ)E(T n,p )] = exp −(1 + o(1))c(δ)p 2 n 2 log 1 p , where c(δ) = min 1 2 δ 2 3 , 1 3 δ , as long as n − 1 42 log n ≤ p ≪ 1. Bhattacharya, Ganguly, Lubetzky, and Zhao [2] generalized this result and were able to compute the upper tail probability Pr[Hom(K, G(n, p)) ≥ (1 + δ)E(Hom(K, G(n, p)))] up to a factor of 1 + o(1) in the exponent for any fixed graph K. With appropriate bounds on p, they were able to compute a constant c(K, δ) such that Pr[Hom(K, G(n, p)) ≥ (1 + δ)E(Hom(K, G(n, p)))] = exp −(c(K, δ) + o(1))p ∆(K) n 2 log 1 p ,…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the answers are often quite different in the G(n, p) and G d n setups. Bhattacharya and Dembo [3] were able to compute the correct log-asymptotic of the probability in the Problem, for graphs K such that the 2-core of K is regular, in a sparse range roughly of the form n 1−ǫ(K) ≪ d ≪ n. (The 2-core of K is given by succesively removing all leaves from K until the minimum degree of K is at least 2, and replacing K by its 2-core does not change the probability in the Problem.) In particular, [3] showed that if the 2-core of K is ∆-regular, then However, [3] left open the question of what happens when the 2-core of K is not regular, only proving that exp −Θ p ∆ n 2 log 1 p (where p = d n and ∆ is the maximum degree of the 2-core of K) is never in fact the correct growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Much less is known about the large deviations of subgraph counts in random graph models beyond G(n, p). This has been studied in the context of random d n -regular graphs [4] and random hypergraphs [16] when the (hyper)-graphs are not too sparse. It is worthwhile to investigate whether the ideas of [12] and this paper can be adapted to these problems to treat sparser regimes.…”
Section: Introductionmentioning
confidence: 99%